(untitled) (Journal of Medicine, 2024)
Megaloblastic anaemia is a common hematological abnormality encountered in clinical practice. We here report a case of 40-year-old male who presented to us with feature of anaemia and typical dermatological manifestation of arsenic intoxication. Complete blood count of patient showed pancytopenia with no circulating atypical cells. Bone marrow examination performed and showed megaloblastic change. Arsenic level in the hair was done and came out very high a. A very few case reports of arsenic causing megablastic anaemia were done in past. Aim of this case report is to create awareness among the physician. J MEDICINE 2024; 25: 90-93